(untitled) (Orfeu, 2019)
The music practiced on a roda de choro is subject to direct and indirect consequences of the interaction and the collectivity. In this article, I seek to demonstrate how this music making provides simultaneous forms of negotiation, promotes instant decisions and offers unique possibilities of organization. Theoretically, I dialogue with authors of ethnomusicology who discuss music making and its possible relations between music and society. Later, I present ethnographic data constructed during my fieldwork, emphasizing negotiation proposals, dynamics of alternation between musicians, and guidelines for choosing the instruments that will be played.